(untitled) (Práxis Educativa, 2024)
The article aims to analyze comparatively the historical evolution that Brazilian universities have had in the three main national rankings: University Ranking Universitario Folha, Guia do Estudante and the ranking generated by the Ministry of Education, the General Course Index (IGC). For this, a bibliographic and documentary analysis of secondary sources of information was carried out. In general, it was detected: (1) there is a set of institutions that are always located in a certain range of positions, regardless of the ranking, the methodology used or the year in question, most of which are public, only two are private, but denominational, philanthropic and non-profit; (2) In Brazil, in a universe of 203 universities, there is a select group of excellence made up of only 13 universities, according to the criteria of the three rankings analyzed. Keywords: Higher Education. University governance. Quality indicators.